Patient Disclosure of Complementary and Integrative Health Approaches in an Academic Health Center. (March 2020) - Connor, Julie; Buring, Julie E; Eisenberg, David M; Osypiuk, Kamila; Davis, Roger B; Wayne, Peter M
Background: Effective patient–doctor communication about complementary and integrative health (CIH) is crucial to coordinate multimodal treatment for complex conditions. While rates of patient disclosure of CIH use to physicians have increased in the United States over the last 30 years, many patients still do not disclose these facts. Integrating CIH approaches within academic medical centers may enhance the communication, but this has not been explicitly studied. Objective: To examine rates of patient disclosure of CIH to physicians and reasons for nondisclosure. Methods: We surveyed 1177 patients at an academic center's CIH clinic regarding their CIH use and disclosure of CIH use to their physician. Results: Of the 1067 who responded to the disclosure questions, 80.1% had discussed their CIH use with their physician, while 19.9% did not. Of those who did not disclose, lack of physician inquiry was reported by 58% as the principal reason. Discussion: Within an academic center, there is still a need to improve communication about CIH use. Possible strategies might include continued education of both patients and physicians about CIH and communication skills and integration of CIH disclosure into routine patient health questionnaires.